MONDAY EFFECT: PENALARANAN LOGIS SEBAGAI AKIBAT DARI PENGARUH PSIKOLOGIS, PENGARUH PERIODE NONPERDAGANGAN, ATAU PENGARUH KOMBINASIAN KEDUANYA (Studi Empiris Berbasis Data Intraday, Bursa Efek Jakarta 1999-2005) - sumiyana sumiyana (Journal of Indonesian Economy and Business (JIEB), 2007)
This research tested Monday effect over day of the week. Especially, this researchinvestigated the existance or not of excessively negative intraday return on Monday which are notidentical in comparison with the same periods in others day. Having identified the existance ofMonday effect, this research continued to investigate the intraday returns on Monday trading andnontrading periods in comparison with intraday return in others day. This study used meancomparison F-test. This research resulted that nontrading weekend effect and psychological effectwere not fully supported, or the both effects were partially and incidentally only. Finally, thisresearch evidenced that Monday effect influenced by combination of nontrading weekend effectand psychological effect.Keywords: monday effect, intraday data, trading periods, nontrading periods, nontrading weekend effect, psychological effect